2019
DOI: 10.1038/s41598-019-46428-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DXA-derived lean mass and MRI-derived cross-sectional area of the thigh are modestly associated

Abstract: Dual-energy X-ray absorptiometry (DXA) derived measures of lean mass demonstrate strong associations with magnetic resonance imaging (MRI) derived measures of muscle volume (MV) in cross-sectional studies, however, few studies have compared changes in response to an intervention. The purpose of this study was to determine the accuracy of DXA at detecting changes in lean mass, using MRI-derived MV as a reference standard. 10 male and 16 female subjects (29.2 ± 9.5 years) underwent DXA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
1
41
1
Order By: Relevance
“…Clark et al [5] noted that while DXA has several advantages as a tool to quantify appendicular lean soft tissue mass, it offers lower accuracy than MRI and CT scans relative to cadaveric measurements and is prone to measurement error. Furthermore, studies have reported only a modest relationship between increases in DXA-and MRIor CT-derived measures of percent change in muscle size [13,20,41]. Thus, we concede that there are a variety of methodological techniques for assessing body composition in both younger and older adults, and measurement via ultrasound, MRI, or CT may yield differing conclusions from those of the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Clark et al [5] noted that while DXA has several advantages as a tool to quantify appendicular lean soft tissue mass, it offers lower accuracy than MRI and CT scans relative to cadaveric measurements and is prone to measurement error. Furthermore, studies have reported only a modest relationship between increases in DXA-and MRIor CT-derived measures of percent change in muscle size [13,20,41]. Thus, we concede that there are a variety of methodological techniques for assessing body composition in both younger and older adults, and measurement via ultrasound, MRI, or CT may yield differing conclusions from those of the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…The legs were isolated using cut-lines that passed through the femoral necks. DXA-derived lean soft tissue mass comprises non-fat and non-bone tissue that correlates well with muscle mass measured using magnetic resonance imaging (MRI) in males and females [29,30].…”
Section: Muscle Mass Assessmentmentioning
confidence: 78%
“…Lean soft tissue mass, a proxy measure for muscle mass, was assessed by whole body dual-energy X-ray absorptiometry (DXA; Lunar Prodigy-Pro, Madison, WI, USA). DXA-derived lean mass comprises non-fat and non-bone tissue and is correlated with skeletal muscle mass measured with magnetic resonance imaging 37 . Appendicular lean mass (ALM) was calculated as the sum of lean mass for the arms and legs and expressed relative to the square of height ALM/height 2 (kg/m 2 ).…”
mentioning
confidence: 99%